TANTANGAN DAN PELUANG DALAM PEMBELAJARAN SEJARAH BERBASIS ARTIFICIAL INTELLIGENCE (AI) PADA ERA DIGITALISASI - Istiqomah, Istiqomah; Syariffudin, Syariffudin; Pamulaan, Alif Bahtiar (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
This article discusses "Challenges and Opportunities in Artificial Intelligence-Based History Learning in the Digital Era". The purpose of this article is to find out the challenges faced by learning in the digital era in artificial intelligence-based history learning and solutions to face educational challenges in the field of artificial intelligence-based history learning in the digital era. The research method used in making this article is a qualitative descriptive method by Explaining the Challenges and Opportunities in Artificial Intelligence (AI)-Based History Learning in the Digital Era. AI-based history learning in the digital era offers many opportunities for innovation and improving the quality of education. However, to take advantage of these opportunities effectively, educators must be prepared to face existing challenges and adapt to rapid changes in educational technology. Further research and development on learning strategies that are responsive to the needs of the times are needed to achieve optimal educational goals in this context.